2018
DOI: 10.1093/cid/ciy631
|View full text |Cite
|
Sign up to set email alerts
|

A Therapeutic Strategy for All Pneumonia Patients: A 3-Year Prospective Multicenter Cohort Study Using Risk Factors for Multidrug-resistant Pathogens to Select Initial Empiric Therapy

Abstract: Japan Medical Association Center for Clinical Trials JMA-IIA00146.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 25 publications
7
45
0
1
Order By: Relevance
“…74,75 Treatment paradigms have also recently been challenged in the empiric treatment of health care-associated pneumonia versus hospital-acquired pneumonia in which empiric therapy is guided by risk factors and severity of illness rather than the likely setting in which the infecting organism was acquired (community vs. health care associated vs. hospital acquired vs. ventilator-associated pneumonia [VAP]). 76 Using this paradigm there was no difference in mortality based on the pneumonia classification and only 4.3% of patients received inappropriate therapy. Whether prior known colonization with resistant gramnegative organisms or prior antibiotic exposure can be used as predictors of future infection with these organisms and guide empiric therapy has been debated.…”
Section: Empiric Therapymentioning
confidence: 92%
“…74,75 Treatment paradigms have also recently been challenged in the empiric treatment of health care-associated pneumonia versus hospital-acquired pneumonia in which empiric therapy is guided by risk factors and severity of illness rather than the likely setting in which the infecting organism was acquired (community vs. health care associated vs. hospital acquired vs. ventilator-associated pneumonia [VAP]). 76 Using this paradigm there was no difference in mortality based on the pneumonia classification and only 4.3% of patients received inappropriate therapy. Whether prior known colonization with resistant gramnegative organisms or prior antibiotic exposure can be used as predictors of future infection with these organisms and guide empiric therapy has been debated.…”
Section: Empiric Therapymentioning
confidence: 92%
“…Unfortunately, recent attempts at developing objective criteria or tools for enhancing the administration of broad-spectrum antibiotics in patients with pneumonia, as well as other serious infections, have met with limited success. [41][42][43][44] A recent randomized controlled trial demonstrated the importance of selecting IAAT in patients with serious infections. Extended spectrum β-lactamases (ESBLs) are commonly found in GNB including Escherichia coli and Klebsiella pneumoniae.…”
Section: Rationale For the Development Of Rdtsmentioning
confidence: 99%
“…In general, recommendations suggest that sicker patients, such as those with shock, should receive broad-spectrum therapy due to the greater potential risks involved with IIAT. 16,41 However, the presence of shock does not necessarily reflect greater likelihood for receiving IIAT and may simply be a reflection of the pathogen's virulence or host factors. 25,26,47 As we suggested recently in an editorial, for patients in the ICU with low acuity of illness, minimal risk factors for antibiotic resistance, and a clinical presentation for which infection is on the differential diagnosis but not the most likely cause, antibiotics could be avoided while awaiting diagnostic testing results.…”
Section: Rationale For the Development Of Rdtsmentioning
confidence: 99%
“…26,32,52,53 Factors, such as increased life expectancy, tend to contribute patients living longer with chronic comorbid conditions and exposed to therapies that may alter the immune system and may be more susceptible to being colonized and at risk of GNB CAP. 6,17,31,54,55 Additional risks, such as exposure to health care systems or interventions, for example, chronic rehabilitation units, nursing homes, or centers where surgeries or hemodialysis are performed, may also increase the risk for GNB CAP. 56,57 Factors related to the development of antimicrobial resistance, such as chronic antibiotic utilization, inappropriate use of antibiotics, and prior antibiotic exposure, may contribute to the higher rates of GNB or MDR GNB observed in certain studies with CAP.…”
Section: Epidemiologymentioning
confidence: 99%
“…Most of these studies come from Europe and Japan. 3,16,17,19,21,22,31,34,35 The main limitation to understand the different prevalence rates of MDR GNB relies on the heterogeneous definitions used in the literature. For example, Prina et al used the acronym of "PES" to identify pathogens not correctly covered by initial empiric treatment in CAP.…”
Section: Prevalence Of Gnb and Mdr Gnb Capmentioning
confidence: 99%